Preserving Culinary Heritage Through Sustainable Gastronomy Event: A Lesson Learn From The 101 Fontana Seminyak - Wijaya, I Nyoman Cahyadi; Shantika, Budi; Sena, I Made Aswin Ananta (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This study investigates the development of a sustainable business model tailored for the convention and event industry within a gastronomy tourism destination context. Focusing on the case study of Gastronomy Feast at The 101 Fontana Seminyak, the research aims to identify key factors contributing to sustainability and propose actionable strategies for enhancing the economic, social, and environmental aspects of the business model. Research methods: A qualitative research approach was employed, utilizing semi-structured interviews, observations, document studies, and literature review. Interviews were conducted with stakeholders involved in organizing and managing Gastronomy Feast events, while observations provided firsthand insights into event operations. Document studies were conducted to supplement primary data, and a comprehensive literature review was undertaken to contextualize the findings within existing knowledge. Results and discussion: The analysis revealed significant findings regarding the sustainable aspects of the business model for Gastronomy Feast at The 101 Fontana Seminyak. Economic sustainability is supported through partnerships with local businesses and revenue diversification. Social sustainability is emphasized through community engagement and cultural preservation. Environmental sustainability is promoted through waste reduction and eco-friendly practices. The discussion explores the interconnectedness of these dimensions and proposes integrated strategies for enhancing overall sustainability. Implication: The findings provide practical insights for stakeholders in the convention and event industry, particularly within gastronomy tourism destinations. By understanding the key factors driving sustainability in the business model of Gastronomy Feast at The 101 Fontana Seminyak, practitioners can adapt similar strategies to promote sustainable development. Additionally, policymakers and destination managers can utilize these insights to formulate supportive policies that encourage the adoption of sustainable practices across the tourism and hospitality sectors. Overall, this study contributes to advancing knowledge and fostering sustainable development in the convention and event industry within gastronomy tourism destinations